Sustainable machining process calculator - A. R., Yusoff; Bagaber, Salem Abdullah; Fawzi, Zamri (2018)
Reducing energy consumption and machining cost under dry condition should considered for sustainable machining. Cutting parameters selection is an important task for dry turning steel and has a significant influence on both the energy consumption and operation cost. In this project, the influence of cutting parameters are namely cutting speed, feed rate and depth of cut on energy, cost and tool wear are firstly analyzed.